COMPARISON OF EFFICACY OF CRYOTHERAPY VERSUS ORAL ZINC SULPHATE IN THE TREATMENT OF CUTANEOUS WARTS - Ali Riaz; Junaid Riaz; Waqas Ahmed; Rabia Mushtaq; Omer Riaz; Komal Mushtaq (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the efficacy of oral zinc sulphate with cryotherapy in the treatment of viral warts.